Implementasi Model Problem Based Learning Pada Mata Pelajaran Dasar-dasar Ketenagalistrikan - Muhammad Rozi Dwi Aprian; Elfizon Elfizon (Departement of Electrical Engineering Universitas Negeri Padang, 2025)
This study aims to determine the effect of implementing the Problem Based Learning (PBL) model on student learning outcomes in the Basic Electrical Engineering course for class X TITL at SMKN 1 West Sumatra in the 2025/2026 academic year. Problem-based learning is applied through the presentation of contextual problems related to basic electrical concepts, including electric current, voltage, resistance, simple electrical circuits, and electrical work safety. During the learning process, students are guided to analyze problems, search for and process information, discuss, and formulate solutions systematically. The research method used is an experimental method with a One-Group Pretest–Posttest Design. The research subjects consisted of 31 students from class X TITL at SMKN 1 West Sumatra. Learning outcome data were obtained through tests administered before (pretest) and after (posttest) the implementation of the PBL mode The research results indicate an increase in the average student learning outcomes after the implementation of the problem-based learning model. The application of the PBL model has been proven effective in improving understanding of basic electrical concepts, critical thinking skills, as well as students' mastery of the material cognitively. With this increase in learning outcomes, students are expected to have a strong knowledge foundation as a basis for studying electrical competencies at the next level.